2011
DOI: 10.1038/pcan.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 Arg399Gln and Arg194Trp polymorphisms in prostate cancer risk: a meta-analysis

Abstract: Epidemiological studies have evaluated the association between X-ray repair cross-complementing group 1 gene (XRCC1) Arg399Gln and Arg194Trp polymorphisms and risk of prostate cancer (PCa). However, the results from the published studies on the association between these two XRCC1 polymorphisms and PCa risk are conflicting. To derive a more precise estimation of association between the XRCC1 polymorphisms and risk of PCa, we performed a meta-analysis. A comprehensive search was conducted to identify all case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…The protein product of XRCC1 is involved in a number of DNA repair pathways, including base excision repair. A previous meta-analysis on XRCC1 and incident prostate cancer failed to identify any association, but recently rs915927 in XRCC1 was shown to be associated with lethal prostate cancer in men with a family history of prostate cancer [34,35]. Though exploratory, our finding supports the biological plausibility that DNA repair genes interact with dietary antioxidants to modulate cancer risk, and is in line with previous reports [36].…”
Section: Discussionsupporting
confidence: 91%
“…The protein product of XRCC1 is involved in a number of DNA repair pathways, including base excision repair. A previous meta-analysis on XRCC1 and incident prostate cancer failed to identify any association, but recently rs915927 in XRCC1 was shown to be associated with lethal prostate cancer in men with a family history of prostate cancer [34,35]. Though exploratory, our finding supports the biological plausibility that DNA repair genes interact with dietary antioxidants to modulate cancer risk, and is in line with previous reports [36].…”
Section: Discussionsupporting
confidence: 91%
“…Such polymorphisms have also been assessed in other types of cancer. Although Wei et al (2011) reported no association with prostate cancer, when they stratified by ethnicity, an in- creased risk for the 399Gln allele in Asian men has been reported. Chen et al (2012) related the Trp/Trp genotype of the XRCC1 Arg194Trp polymorphism to an increased risk of gastric cancer, while Huang et al (2009) associated dominant and recessive models for XRCC1 Arg399Gln polymorphism with breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…The Arg399Gln polymorphism (rs25487) is located at the region of the BRCT-I interaction domain of XRCC1 and is linked with the reduced DRC (56,57). This polymorphism has been extensively investigated for its associations with cancer risk and the results were conflicting in different types of cancer or different populations (58)(59)(60)(61); however, a meta-analysis including 7 studies indicated that Arg399Gln was not significantly associated with SCCHN risk in Caucasians and/or Asians (25), consistent with our findings in this study.…”
Section: Discussionmentioning
confidence: 99%